47.2k views
4 votes
Using the completing-the-square method, rewrite f(x) = x2 − 8x + 3 in vertex form. f(x) = (x − 8)2 f(x) = (x − 4)2 − 13 f(x) = (x − 4)2 + 3 f(x) = (x − 4)2 + 16

User KiwenLau
by
4.7k points

1 Answer

3 votes

Answer:

f(x) = (x - 4)² - 13

Explanation:

Given

f(x) = x² - 8x + 3

To complete the square

add/subtract ( half the coefficient of the x- term )² to x² - 8x

f(x) = x² + 2(- 4)x + 16 - 16 + 3 = (x - 4)² - 13

User DerKorb
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.